The effect of student-centred learning approaches in physical education on positive youth development - Risyanto, Aris; Subarjah, Herman; Ma'mun, Amung; Nuryadi; Prabowo, Indra (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2024)
Background Problems: Recognising the pivotal role of holistic development and positive youth development in empowering young individuals, physical education emerges as a crucial component for fostering comprehensive growth in children. Research Objectives: This study seeks to provide valuable insights to enhance the implementation of physical education programmes in schools, aiming to facilitate positive growth among teenagers in both physical and psychosocial dimensions. Methods: Employing a play-teach-play (PTP) treatment, this research engaged students from Public Junior High School in Sidamulih. The study population comprised four classes of class VIII students, totaling 94 participants. The students were divided into two groups: Class VIII B (experimental group, n = 23) and Class VIII D (control group, n = 23). These groups were given the PTP treatment, and the independent sample t-test was used to compare changes in Positive Youth Development (PYD) between the two groups at the statistical level. Findings/Results: The study revealed a significant difference in PYD growth between teenagers participating in the play-teach-play programme and the control group. These results underscored the efficacy of the PTP strategy in promoting healthy teenage development within the realm of physical education. Conclusion: This research provides compelling evidence supporting the effectiveness of the play-teach-play (PTP) approach in fostering positive youth development (PYD) during adolescence. The data emphasises the impactful role of student-centred learning methods in adolescent development. The study's findings underscore the importance of incorporating such approaches into instructional strategies to empower students to achieve their academic potential fully. This contributes significantly to the evolving body of knowledge and practices in the field of education.